Numerical Development of a Re-centering Damper with High Seismic Performance, Including Friction Wedges and SMA Rods (Journal of Civil Engineering Researchers, 2025)
Re-centering dampers, developed using shape memory alloy (SMA)-based dampers and their superelasticity capability, absorb earthquake energy and provide a re-centering capability for the structure. In this study, the laboratory sample of Zhang's re-centering damper was first validated using ABAQUS software, followed by parametric analysis involving changes in the number and diameter of SMA rods, the friction coefficient of the wedges, and the placement configuration of two dampers, which were numerically investigated. The results indicated that increasing the diameter and number of rods, as well as the friction coefficient, enhances seismic resistance and stiffness but reduces ductility; excessive increase in friction only boosts the stiffness and ductility of the damper's compressive section while reducing seismic resistance. A friction coefficient of approximately 0.12 is recommended, whereas Zhang assumed 0.09. Additionally, the results showed: in parallel configuration, resistance and stiffness are higher but ductility is lower, whereas in series configuration, all three parameters decrease.
Keywords: Numerical Development; Re-Centering Damper; SMA; Friction Wedge